Analysis of the Impact of Transformational Leadership on Organizational Commitment and Job Satisfaction - Iryadana, Mohamad Razab (Sharia Business Management Department of STEBIS Bina Mandiri, 2024)
This research was carried out with the main aim of analyzing the influence that transformational leadership has on two important aspects in an organization: organizational commitment and employee job satisfaction. Transformational leadership, known for its capacity to inspire and motivate employees, is considered a key factor that can increase both organizational commitment and job satisfaction. Using a qualitative approach, this research in-depth examines how this leadership style influences employees' perceptions and attitudes towards the entity where they work. The research results confirm that transformational leadership plays a vital role in forming a stronger commitment from employees to their organization and increasing their level of satisfaction with their work. This higher organizational commitment and greater job satisfaction was further identified as having a significant contribution to improving overall organizational performance. Based on these findings, it is recommended that organizations strive to develop and maintain transformational leadership practices as a strategy to improve their internal quality, which includes increasing employee commitment and job satisfaction. The implementation of this leadership style is expected to encourage the creation of a more positive and productive work environment, which will ultimately benefit both employees and the organization as a whole.